Increasing Rates of Carbon Burial in Southwest Florida Coastal Wetlands. Issue 2 (18th February 2020) - Breithaupt, Joshua L.; Smoak, Joseph M.; Bianchi, Thomas S.; Vaughn, Derrick R.; Sanders, Christian J.; Radabaugh, Kara R.; Osland, Michael J.; Feher, Laura C.; Lynch, James C.; Cahoon, Donald R.; Anderson, Gordon H.; Whelan, Kevin R.T.; et al.
Abstract: Rates of organic carbon (OC) burial in some coastal wetlands appear to be greater in recent years than they were in the past. Possible explanations include ongoing mineralization of older OC or the influence of an unaccounted‐for artifact of the methods used to measure burial rates. Alternatively, the trend may represent real acceleration in OC burial. We quantified OC burial rates of mangrove and coastal freshwater marshes in southwest Florida through a comparison of rates derived from 210 Pb, 137 Cs, and surface marker horizons. Age/depth profiles of lignin: OC were used to assess whether down‐core remineralization had depleted the OC pool relative to lignin, and lignin phenols were used to quantify the variability of lignin degradation. Over the past 120 years, OC burial rates at seven sites increased by factors ranging from 1.4 to 6.2. We propose that these increases represent net acceleration. Change in relative sea‐level rise is the most likely large‐scale driver of acceleration, and sediment deposition from large storms can contribute to periodic increases. Mangrove sites had higher OC and lignin burial rates than marsh sites, indicating inherent differences in OC burial factors between the two habitat types. The higher OC burial rates in mangrove soils mean that their encroachment into coastal freshwater marshes has the potential to increase burial rates in those locations even more than might be expected from the acceleration trends. Regionally, these findings suggest that burial represents a substantially growing proportion of the coastal wetland carbon budget. Plain Language Summary: Coastal mangroves and marshes use photosynthesis to change carbon dioxide into plant material like leaves, wood, and roots. As these materials die over time, they do not decompose the same way they might in a dry soil environment. Instead, daily ocean tides flood the soil, removing the oxygen and allowing dead plant materials to be buried and preserved for hundreds to thousands of years or more. This "carbon burial" process is a global benefit because it means that carbon dioxide, a greenhouse gas, is stored belowground where it can no longer warm the atmosphere. Mangroves and marshes bury carbon more quickly than most other ecosystems, but little is known about how burial rates change over time. In this study, we quantify how rates of carbon burial have changed in southwest Florida coastal wetlands in the past century. We find that carbon burial is 2.5–4.5 times greater today than it was a century ago in mangroves and 1.9–2.3 times greater in marshes. We propose sea‐level rise as the most likely cause of increased carbon burial. Rising seas provide the means and opportunity for wetlands to bury more carbon, but if sea level rises too quickly, these wetlands may drown. Key Points: Organic carbon burial rates increased by factors of 2.5 to 6.2 for mangroves and 1.4 to 2.4 for coastal freshwater marshes in the past ~120 years Increasing rates represent acceleration rather than a record influenced by an artefact of the dating method or postdepositional degradation Acceleration has increased soil carbon stocks by 5.7–8.0 kg m −2 for mangroves and 4.2–4.5 kg m −2 for coastal freshwater marshes